Disentangling conscious and unconscious processing: a subjective trial-based assessment approach - Van Den Bussche, Eva; Vermeiren, Astrid; Desender, Kobe; Gevers, Wim; Hughes, Gethin; Verguts, Tom; Reynvoet, Bert (Frontiers in Human Neuroscience, 2013)
The most common method for assessing similarities and differences between conscious and unconscious processing is to compare the effects of unconscious (perceptually weak) stimuli, with conscious (perceptually strong) stimuli. Awareness of these stimuli is then assessed by objective performance on prime identification tasks. While this approach has proven extremely fruitful in furthering our understanding of unconscious cognition, it also suffers from some critical problems. We present an alternative methodology for comparing conscious and unconscious cognition. We used a priming version of a Stroop paradigm and after each trial, participants gave a subjective rating of the degree to which they were aware of the prime. Based on this trial-by-trial awareness assessment, conscious, uncertain and unconscious trials were separated. Crucially, in all these conditions, the primes have identical perceptual strength. Significant priming was observed for all conditions, but the effects for conscious trials were significantly stronger, and no difference was observed between uncertain and unconscious trials. Thus, awareness of the prime has a large impact on congruency effects, even when signal strength is controlled for.